2021
DOI: 10.1002/adhm.202101151
|View full text |Cite
|
Sign up to set email alerts
|

Yields and Immunomodulatory Effects of Pneumococcal Membrane Vesicles Differ with the Bacterial Growth Phase

Abstract: Streptococcus pneumoniae infections are a leading cause of death worldwide. Bacterial membrane vesicles (MVs) are promising vaccine candidates because of the antigenic components of their parent microorganisms. Pneumococcal MVs exhibit low toxicity towards several cell lines, but their clinical translation requires a high yield and strong immunogenic effects without compromising immune cell viability. MVs are isolated during either the stationary phase (24 h) or death phase (48 h), and their yields, immunogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Until now, some attempts have been made to use MV vaccines in fish with varying results depending on the fish species 47 51 . One reason for the inconclusive data could be the variability of MV proteomes, as the protein composition has been reported to differ with growth phase 52 , 53 , cultivation media 54 , bacterial strain 55 , the MV extraction protocol 54 , 56 or even the size of the vesicles 52 . Defined production conditions and detailed characterization of the MVs are therefore crucial for the successful application of MV vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, some attempts have been made to use MV vaccines in fish with varying results depending on the fish species 47 51 . One reason for the inconclusive data could be the variability of MV proteomes, as the protein composition has been reported to differ with growth phase 52 , 53 , cultivation media 54 , bacterial strain 55 , the MV extraction protocol 54 , 56 or even the size of the vesicles 52 . Defined production conditions and detailed characterization of the MVs are therefore crucial for the successful application of MV vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the averaged diameter of 103 + -EVs (130 nm) is slightly bigger than 103 − -EVs (105 nm) ( Figure 1 ). The size of EVs in Gram-positive bacterial varies between different bacterial strains [ 34 , 35 , 36 , 37 ], throughout various stages of bacterial growth [ 38 ], and environmental conditions [ 27 , 39 , 40 ]. As the reports that the size distribution of EVs of the invasive Streptococcus pyogenes strains SSI-1 were 1.31 times bigger than the non-invasive Streptococcus pyogenes strains JRS4 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene ID, chromosomal locations, number of nucleotides in genomic DNA and mRNA, and number of exons were identified by using the NCBI gene database ( ). The subcellular localization of K + transporting proteins was predicted by using a web-based tool ProtCamp 9.0 (ProtComp—Predict the sub-cellular localization for Plant proteins (softberry.com), and then, these locations were also verified by another online tool, CELLO v.2.5 ( ), by using protein sequences of K + transporting gene family ( Garg et al., 2016 ; Mehanny et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The subcellular localization of K + transporting proteins was predicted by using a web-based tool ProtCamp 9.0 (ProtComp-Predict the sub-cellular localization for Plant proteins (softberry.com), and then, these locations were also verified by another online tool, CELLO v.2.5 (http://cello.life. nctu.edu.tw/), by using protein sequences of K + transporting gene family (Garg et al, 2016;Mehanny et al, 2022).…”
Section: Physiochemical Properties Of K + Transporting Gene Family Me...mentioning
confidence: 99%